Self-Efficacy Profile of Junior High School Students and Implications for Guidance and Counseling Services - Rina Yulitri; Aura Ariani; Ardimen Ardimen; Rafsel Tas'adi; Desri Jumiarti (Journal of Islamic Education Students (JIES), 2023)
Self-efficacy plays a crucial role that should be instilled in every individual as it significantly impacts one's success. This research aims to assess the level of self-efficacy among junior high school (SMP) students and its implications for guidance and counseling services. The study adopts a survey design with a population of SMP students and a sample of 87 students selected through simple random sampling. The research instrument used is a self-efficacy scale, and data analysis is conducted using descriptive quantitative methods. The research findings indicate that SMP students have a moderate level of self-efficacy. These results can serve as a reference for guidance and counseling teachers to assist students in enhancing their self-efficacy.